Improving English Vocabulary Mastery through Wordwall-Based Gamification: A Quasi-Experimental Study - Irmayanti; Velmi Mayaputri; Nur Syamsiyah Ekhsan (Jurnal Bahasa Inggris Terapan, 2025)
In learning English, students often struggle to maintain enthusiasm and interest because language learning is perceived as boring. Therefore, teachers need to be selective in applying appropriate teaching methods and techniques. These methods are essential for helping teachers achieve learning objectives. To sustain student engagement in English lessons, games can serve as an effective alternative. One such approach is gamification, which integrates game elements and mechanics into learning to boost students' motivation and interest. This study investigates the effectiveness of gamification using Wordwall in enhancing students' vocabulary mastery at MIS Muhammadiyah Wuring, Maumere during the 2024-2025 academic year. The research adopts a quantitative approach with a quasi-experimental design and purposive sampling, involving two fourth-grade classes an experimental class using Wordwall and a control class (p < 0.05) without it with involving the fourth-grade students of MIS Muhammadiyah Wuring. Data were collected through pre-tests and post-tests, then analyzed using simple linear regression in SPSS 22. Findings show a notable improvement in vocabulary mastery in the experimental class. This supports gamification, especially Wordwall, as an effective tool in engaging students and enhancing vocabulary skills in English learning. This study adds to previous gamification and Wordwall research by providing quantitative experimental evidence from an elementary Islamic school context, specifically involving fourth-grade students, and by statistically measuring the effect of Wordwall-based gamification on vocabulary mastery using simple linear regression analysis.